(untitled) (Raparin Journal of Humanities (RJH), 2026)
The aims of research are to Understand the level of Technological Applications in Kindergarten from the Perspective of Teachers. And understand the level of Learning Motivation Performance of kindergarten Children from the Perspective of Teachers. And to show the relationship between Technological Applications and Learning Motivation Performance of kindergarten Children from the Perspective of Teachers. In this study, the researcher employed descriptive survey methods. For the Purpose of this research, the Technological Applications scale developed by Alsaeed, and etc (2019), Consisting of 16 items. Furthermore, the Learning Motivation scale designed by Alsamawi (2018), compressing 16 items. Upon extracting the Scientific criteria, including construct validity and interna consistency, the research sample was divided into 93 teachers. The teachers were selected using simple random sampling. Statistical analyses, including one sample t-test, means, and Pearson correlation coefficients, were then applied. The result of Technological Applications in Kindergarten is perceived to at medium from the Perspective of Teachers. the level of Learning Motivation Performance of kindergarten Children is perceived to at medium from the Perspective of Teachers. And additionally, a weak positive statistical relationship was found between the Technological Applications and Learning Motivation. Based on the result, several recommendations and suggestions were Presented.